Автономне навчання - Самаріна, В. В.; Шахматова, Олена Вікторівна (Видавничий дім "Гельветика", 2020)
У статті досліджується зміст поняття "автономне навчання" та основні характеристики. Акцентується увага на тому, що викладач організовує навчальну діяльність на партнерських засадах, мотивує та підтримує пізнавальний інтерес до навчання, є помічником та консультантом у навчальній діяльності. Складовим елементом автономного навчання є самоконтроль як важливе джерело інформації про очікування та потреби студентів, їхні проблеми, їхня реакція на використовувані в навчальному процесі матеріали й методи. Для розвитку індивідуальної автономії учня завжди необхідна взаємодія із соціальним середовищем. Відповідно, необхідно знайти баланс між свободою, яку можуть і повинні мати ті, хто вивчають мову, і діяльністю, що контролюється навчальним середовищем. Автономне навчання розглядається як одна з технологій особистісно-орієнтованого навчання, що забезпечує самовизначення та самореалізацію студента у процесі оволодіння іноземною мовою.

The article is aimed to discuss a variety of meanings of the concept of autonomy. On a general level it can be said that all learning is autonomous, since it is based on the mental activities of an individual, not learning autonomously would be as impossible as not communicating. Regardless of particular methods used in teaching, it is always the learner alone ("autonomously") who makes sense of the input and links new "data" with existing knowledge. There is an educational dimension, in which the development of autonomy is seen as a prerequisite for the assumption of social responsibility. The study of autonomy is understood as a contribution to the discussion about humane education in general, whereby autonomy stands for maturity, emancipation and self-determination. This discussion is general and not related to foreign language learning, but it should remind one that foreign language learning also contributes to humane education and by emphasizing an aspect such as dealing with alterity. The essence of learner autonomy is acceptance of responsibility for one’s own learning. This entails establishing a personal agenda for learning, taking at least some of the initiatives that shaped the learning process, and developing a capacity to evaluate the extent and success of one’s learning. From this definition it follows that learner autonomy entails not only learning, but learning how to learn. Interpreted in this way, it can be developed in any learning environment and within any organizational framework. A differentiation between learner autonomy and self-directed learning can be mentioned. According to this, self-directed learning actions can be understood as the practical implementation of learner autonomy. According to this, learner autonomy would rather refer to the characteristics and self-directed learning more than to the activities of learners. But the understanding of learner autonomy also appears to be greatly simplified in other areas and therefore problematic, as it will be explained below. learner autonomy is often seen as a key competence that one would urgently need in a working world that is constantly changing. This understanding of the term is accompanied by the risk that learner autonomy is perceived primarily as an optimization of learner performance. For the development of individual learner autonomy, interaction with the social environment is always necessary. Accordingly, a balance must be found between the freedom that language learners can and should have and the activities controlled by the learning environment, such as instructions and support from the teacher or other learners.
Autonomous learning
Keywords: стратегії навчальні; процес навчальний; технології навчальні; teaching strategies; educational process; teaching technologies